GENE-08. SECONDARY GLIOBLASTOMA, IDH-WILDTYPE ARISING IN DIFFUSE ASTROCYTOMA, IDH-MUTANT: A CASE REPORT - Sang Lee, Kyu (Neuro Oncol, 2019)
Primary glioblastoma develops de novo without clinical or histological evidence of a low-grade precursor lesion, while secondary glioblastoma develops from a low-grade glioma. The same IDH mutation is observed in almost secondary glioblastomas that occurs in low-grade gliomas with IDH mutation. Present report is an extraordinary case of secondary glioblastoma, IDH-wildtype arising in diffuse astrocytoma, IDH-mutant. A 31-year-old female presented with seizure 3 months ago, who had a history of operation for diffuse astrocytoma, IDH-mutant on the left frontal lobe 6 years ago. Magnetic resonance imaging test revealed new infiltrative lesions (6.5cm) in left frontal lobe and corpus callosum, in addition to the non-enhancing mass (3.4cm). New infiltrative lesion suspected anaplastic change and the patient underwent tumorectomy. Microscopically, non-enhancing lesion showed high cellularity, moderate nuclear atypia and brisk mitosis. Microvascular proliferation and necrosis were absent that can be diagnosis as anaplastic astrocytoma. However, new infiltrative lesion showed microvascular proliferation and necrosis that acceptable for diagnosis as glioblastoma. IDH-1 immunohistochemistry (IHC) was positive in anaplastic astrocytoma but negative in glioblastoma. In addition, we assessed NGS based on the SNUBH Brain v1.0 (Macrogen, Seoul, South Korea) panel. Similar to IHC result, IDH-1 (p.Arg132His) mutation was found in anaplastic astrocytoma but not in glioblastoma. Interestingly, ATRX (p.Gln1670Ter) and TP53 (p.His193Arg) mutations were found in both lesions. Additionally, PTEN (p.His296Pro) mutation was identified in glioblastoma component only. Until now, it is well-known hypothesis that the IDH mutation initiated in glial progenitor cell and the other genetic mutations occur sequentially in pathogenesis of secondary glioblastoma. Notably, this is the first case report that other genetic alterations can be initiated before IDH mutation contrary to previous hypothesis. In our case, mutation of ATRX and TP53 might be initiated, and PTEN and IDH-1 mutations were sequentially occurred in glioblastoma and anaplastic astrocytoma, respectively.